RANCANG BANGUN APLIKASI ANALISIS PERENCANAAN KEBUTUHAN TENAGA KESEHATAN MENGGUNAKAN METODE WISN (STUDI KASUS RSIA PRIMA HUSADA) - Cahyono, Agus; Sudarmaningtyas, Pantjawati; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract: Mother and child hospital is a hospital that provide health services and medical services for the surrounding community. Health services and medical provided to the public is not optimal, this is because lack of the number of health workers that led to the average waiting time patients who do not meet standard prescribed by health department. The process of planning needs analysis of health workers in RSIA currently only reference to the rules of health minister regulation no. 340/MenKes/PER/III/2010 about a minimal amount of health to be owned and not consider their workload. While ideally in determining the amount of health workers have to consider their workload. It takes an appropriate solution that is using a method of WISN (Workload Indicator Staff Need) in the process of planning needs analysis of health workers based on their workload and can give a total number of optimal health workers needed. Results from the trial of research and evaluation of this final project research is that produce an application of planning needs analysis of health workers using methods WISN (Workload Indicator Staff Need) which can facilitate the user in determining the amount of planning needs of health workers required